2017
DOI: 10.1007/s11095-017-2206-3
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated and Entrapped HPMA-PLA Nano-Polymeric Micelles Based Dual Delivery of First Line Anti TB Drugs: Improved and Safe Drug Delivery against Sensitive and Resistant Mycobacterium Tuberculosis

Abstract: RIF loaded and INH conjugated HPMA-PLA polymeric micelles (PMRI) were more effective against sensitive and resistant M tuberculosis. The developed approach can lead to improved patient compliance and reduced dosing in future, offering improved treatment of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…And due to hydrophobic interaction, it is easily loaded into the hydrophobic core, with high drug solubility [ 20 , 21 ]. Previous research [ 22 ] has shown that the formation of HPMA-PLA-RIF copolymer micelles enhanced the efficacy of drugs, improved the solubility of drugs, and combated the resistance of tuberculostatics. To observe whether HPMA-PLA has toxicity to macrophages, we intervened with infected or uninfected macrophages with HPMA-PLA without drug loading.…”
Section: Discussionmentioning
confidence: 99%
“…And due to hydrophobic interaction, it is easily loaded into the hydrophobic core, with high drug solubility [ 20 , 21 ]. Previous research [ 22 ] has shown that the formation of HPMA-PLA-RIF copolymer micelles enhanced the efficacy of drugs, improved the solubility of drugs, and combated the resistance of tuberculostatics. To observe whether HPMA-PLA has toxicity to macrophages, we intervened with infected or uninfected macrophages with HPMA-PLA without drug loading.…”
Section: Discussionmentioning
confidence: 99%
“…7−9 For example, these systems enhance the therapeutic effectiveness and minimize the undesirable side effects of numerous antibacterial drugs. 5,10 In this context, several types of anti-TB nanoformulations including for example solid lipid nanoparticles, 7,11 inorganic nanoparticles, 8,12,13 micelles, 14 and polymeric nanoparticles 15−18 have been utilized. In other words, a wide variety of nanocarriers and biomaterials have been explored for mono-and multidrug delivery in TB.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, several types of anti-TB nanoformulations including for example solid lipid nanoparticles, , inorganic nanoparticles, ,, micelles, and polymeric nanoparticles have been utilized. In other words, a wide variety of nanocarriers and biomaterials have been explored for mono- and multidrug delivery in TB.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a su biocompatibilidad, estabilidad estructural, alta capacidad de transportar medicamentos en su superficie externa y de solubilizar medicamentos hidrofóbicos en su núcleo interno, tienen ventajas sobre otras NP para transportar diversos tipos de fármacos. Detalles sobre la evaluación de estas NP para transportar rifampicina se puede encontrar en la Tabla 5 (45)(46)(47)(48)(49) .…”
Section: Nanomicela (Nmc)unclassified